2014
DOI: 10.1007/s40593-014-0015-y
|View full text |Cite
|
Sign up to set email alerts
|

Carelessness and Affect in an Intelligent Tutoring System for Mathematics

Abstract: We investigate the relationship between students' affect and their frequency of careless errors while using an Intelligent Tutoring System for middle school mathematics. A student is said to have committed a careless error when the student's answer is wrong despite knowing the skill required to provide the correct answer. We operationalize the probability that an error is careless through the use of an automated detector, developed using educational data mining, which infers the probability that an error invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 57 publications
(87 reference statements)
0
5
0
Order By: Relevance
“…In this study, this showed that although pupils' errors were often due to misconceptions, the teacher need to be aware that pupils can and do made careless errors. This type of errors may occur because pupils were competitive and rush in their work to finish it [16,45] stated that pupils who frequently experience involvement of concentration in mathematics, displayed carelessness. On the other hand, Clement [23] stated that there was a positive relationship between carelessness and confidence, such that pupils who understand the content and believed that they can answer the problem, made higher percentage in careless errors.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, this showed that although pupils' errors were often due to misconceptions, the teacher need to be aware that pupils can and do made careless errors. This type of errors may occur because pupils were competitive and rush in their work to finish it [16,45] stated that pupils who frequently experience involvement of concentration in mathematics, displayed carelessness. On the other hand, Clement [23] stated that there was a positive relationship between carelessness and confidence, such that pupils who understand the content and believed that they can answer the problem, made higher percentage in careless errors.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, as a general synthesis, in Table 2, a list of papers from 2012 to date arranged chronologically are shown, these articles were selected because they include one or more of the topics analyzed in this paper, plus the main theme that has to see with Tutorial Systems. The first column of Table 2 (tagged with R) indicates the reference of the paper, the numbers of the other columns, organized as follows, indicate the topics in [20] x x x 1 [27] x x x x x 22 [47] x x x 2 [48] x x 48 [44] x x x x 0 [13] x x x 12 [24] x x 0 [40] x x x x 1 [49] x x x 1 [50] x x x x 35 [42] x x x 0 [51] x x x x x x 33 [52] x x x x 1 [53] x x x x x 13 [33] x x 1 [54] x x x 327 [30] x x x x 1 [21] x x x x 1 [38] x x x 3 [36] x x x x x 7 [6] x x x x 4 [28] x x x x x 26 [4] x x x 0 [55] x x x 6 [14] x x x 17 [5] x x x x 20 [19] x x x 5 [56] x x x 18 [45] x x 9 [57] x x x 195 [37] x x 3 [16] x…”
Section: Summary Of Art State Analysismentioning
confidence: 99%
“…On the negative side, use of such systems are known to create disengagement in the users' minds. As mentioned in [3] the different forms of disengagement from the task at hand include engaging in off-task behavior such as net-surfing, exploiting system's features in a quiz such as repeated guessing, working carelessly and using the system in ways unrelated to the stated work. It has been pointed out that boredom and confusion precede such behaviors although such computer-based learning systems are seen to be quite engaging in general and are useful when the number of students in a class is large.…”
Section: Introductionmentioning
confidence: 99%